Marker assisted screening of Nepalese wheat genotypes and advanced lines for resistance to different races of wheat rust species - Sharma, S.; Ghimire, S. K.; Niroula, R. K.; Ojha, B. R.; Thapa, D. B. (Journal of the Institute of Agriculture and Animal Science, 2018)
Primers tightly linked to genes of interest are valuable tools in rust resistant wheat breeding. A research was conducted with the objective to detect the source of rust resistant genes and further utilize as an important weapon in gene pyramiding. A total of forty gene-specific primer sets consisting of Lr, Yr and Sr associated gene specific markers were applied for screening thirty wheat genotypes. Based on the value of band size, the presence of concerned resistance gene was predicted and binary scoring was done for further analysis. Softwares Genealex and NTSYSpc2.1 were applied for detail analysis. Some genes like Lr29, Lr51, YrCH42, Sr36, etc. were detected in many of the tested genotypes but some genes like Lr47, Sr39, Sr24 were absent in tested lines. Among tested genotypes, Chyakhura-1 possesses highest number of rust resistant genes and Annapurna-4 bears lowest number of genes. Highest value of Jaccard coefficient was obtained between genotypes Danphe-1 and Danphe-2 (0.87) showing their greatest resemblance. UPGMA dendrogram grouped thirty genotypes into distinct four clusters. Percentage of Polymorphic loci was 88.57 and grand mean of observed heterozygosity (Ho) was found to be 0.193 (S.E 0.057). Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 165-175